Involving teachers in reducing children's media risks. Issue 1 (2nd January 2018) - Stiller, Anja; Schwendemann, Hanna; Bleckmann, Paula; Bitzer, Eva-Maria; Mößle, Thomas
Abstract : Purpose: The purpose of this paper is twofold: first, to introduce MEDIA PROTECT, a multi-modal intervention for parents and teachers with six components preventing problematic, and in the long run addictive, use of screen media by children; second, to present results of a formative evaluation of the teacher training, an important component of the intervention. Design/methodology/approach: In presenting the intervention, the authors used a common framework to describe complex interventions systematically. For the evaluation, participants were recruited from German schools and kindergarten for a cluster-controlled trial. As part of a formative evaluation, the participants completed written questionnaires to determine the importance of different components of the intervention in addition to their overall satisfaction. Additional qualitative interviews with teachers were conducted. Findings: The authors recruited n =50 kindergartens and n =9 schools; n =30 received the intervention. N =222 teachers participated in the training and n =192 completed the questionnaire (86 per cent). Seven qualitative interviews were conducted. Participants exhibited high levels of overall satisfaction with the training, considered it moderately to highly relevant to their work, and exhibited varying satisfaction levels with different components and multipliers. The qualitative data support these findings. Originality/value: Few interventions to date have pursued a universal approach to the prevention of problematic screen media use. This evaluation of MEDIA PROTECT is the most recent study in Germany, which involves a complex programme through which teachers are taught ways to promote the age-adequate use of screen media in the family, parents are provided with guidance and healthy leisure time activities for children are fostered.